Community-Based Livestock Breeding: Coordinated Action or Relational Process? - Wurzinger, Maria; Gutiérrez, Gustavo A.; Sölkner, Johann; Probst, Lorenz (Frontiers in Veterinary Science, 2021)
Over the past decade, community-based breeding programs (CBBPs) have been promoted as a viable approach to improving smallholder livelihoods through a systematic livestock breeding. CBBPs aim to initiate systematic breeding at the community level, including an organized animal identification and recording of performance and pedigree data. To ensure the breeding programs' continuity, building capacities, and ownership among participants are essential to the approach. This study's purpose was to understand how CBBPs have evolved in specific institutional settings and which dynamics occur in the course of implementation. We addressed these questions in reflective conversations with six coordinators of a diverse sample of CBBPs: goats (Malawi, Uganda, and Mexico), sheep (Ethiopia), alpaca (Peru), and cattle (Burkina Faso). The interviews and analysis were guided by categories of the multi-level perspective. The respondents considered lack of funding and weak institutionalization as the main constraints on the CBBPs. While the idea of participation and localized ownership was at the center of the programs, linear paradigms of knowledge transfer prevailed. In all cases, the impulse to start a CBBP came from individual researchers, who relied on intermediaries, such as extension agents, for implementation. Personal relations and trust were seen as both a factor in the success and a positive outcome of CBBPs. We conclude that these findings have different implications depending on how rural development is conceptualized: proponents of the innovation systems perspective would call for stakeholders to further align their interests and coordinate their actions. Proponents of process-relational concepts, in contrast, would not consider the CBBP a product but a starting-point for initiators and participants to continuously discover new ways of collaboration and engagement.